Beyond cellulose: pharmaceutical potential for bioactive plant polysaccharides in treating disease and gut dysbiosis - Niu, Yuanlin; Liu, Wei; Fan, Xueni; Wen, Dongxu; Wu, Dan; Wang, Hongzhuang; Liu, Zhenjiang; Li, Bin (Frontiers in Microbiology, 2023)
Polysaccharides derived from plants, algae, or fungi serve as the major components of some human diets. Polysaccharides have been shown to exhibit diverse biological activities in improving human health, and have also been proposed to function as potent modulators of gut microbiota composition, thus playing a bi-directional regulatory role in host health. Here, we review a variety of polysaccharide structures potentially linked to biological functions, and cover current research progress in characterizing their pharmaceutical effects in various disease models, including antioxidant, anticoagulant, anti-inflammatory, immunomodulatory, hypoglycemic and antimicrobial activities. We also highlight the effects of polysaccharides on modulating gut microbiota via enrichment for beneficial taxa and suppression of potential pathogens, leading to increased microbial expression of carbohydrate-active enzymes and enhanced short chain fatty acid production. This review also discusses polysaccharide-mediated improvements in gut function by influencing interleukin and hormone secretion in host intestinal epithelial cells.